(untitled) (Current Horticulture, 2024)
The genetic diversity in morphological and physico-chemicaltraits of nine genotypes of litchi (Litchi chinensis Sonn.) growing under the agroclimatic conditions of Bihar was studied during 2018-19. The genotypes IC-0614730 and IC-0614737 exhibited bright pink colour of young leave and others had yellowish green. Its fruit shape and colour was round and deep pink, respectively. Pink flushes genotypes were late, while yellowish green were early in maturity. These two genotypes showed lowest fruit weight (17.35 g and 16.38 g), TSS (17.86 and 18.35 Brix), seed content (10.66% and 11.97%) but higher pulp content (71.18% and 74.66%). Significant variations were recorded in phenolics and flavonoids contents among the genotypes with highest content in both IC-0614730 and IC-0614737. These two genotypes can be potentially exploited in litchi industry for pulp making and nutraceutical uses. The genotypes differed in most of the morphological characteristics which can be exploited for improvement in litchi.